Experimental Characterization of C–C Composite Destruction Under Impact of High Thermal Flux in Atmosphere and Hypersonic Airflow - Ryan Bencivengo; Alin Ilie Stoica; Sergey B. Leonov; Richard Gulotty (Aerospace)
Hypersonic flight in the atmosphere is associated with high thermal flux impacting the vehicle surface. The nose, leading edges, and some elements of the engine typically require the implementation of highly refractory materials or an active thermal protection system to maintain structural stability during the vehicle mission. Carbon–carbon (C–C) composites are commonly considered for the application thanks to their unique thermal and mechanical properties. However, C–C composites’ ablation and oxidation under long cruise flights at high speeds (Mach number > 5) are the limiting factors for their application. In this paper, the results of an experimental study of C–C composite thermal ablation and oxidation with test article surface temperatures up to 2000 K are presented. The tests were performed under atmospheric conditions and hypersonic flow in the ND_ArcJet facility at the University of Notre Dame. The test articles were preheated with CW laser radiation and then exposed to M = 6 flow at stagnation pressures up to 14 bar. It was found that C–C composite oxidation and mechanical erosion rates are significantly increased in hypersonic airflow compared to those at ambient conditions and nitrogen M = 6 flow. Compared to atmospheric air, mass loss occurred at a rate of 1.5 orders of magnitude faster for M = 6 airflow. During high-speed flow conditions, rapid chemical oxidation and the mechanical destruction of weakened C-fibers likely cause the accelerated degradation of C–C composite material. In this study, a post-mortem microscopic analysis of the morphology of the C–C surface is used to explain the physical processes of the material destruction.